Cidade versus universidade: um estudo de caso sobre a dinâmica entre munícipes e a vida universitária em São Carlos - Queirantes, Sabrina (Universidade Federal de São Carlos, 2024)
Over the last few years, Brazilian public universities have been subjected to financial and ideological attacks against their existence. The following research aims to understand the relationship between public universities and the general population, by analyzing discourse, opinions and activities on social media, especially in a conservative and neoliberal political scenario, as well as carrying out a historical and theoretical recovery of the higher education scenario in Brazil. To this purpose, a case study of the municipality of São Carlos will be carried out, given that the city has two public universities, the University of São Paulo (USP) and the Federal University of São Carlos (UFSCar), and is known as a technology and science hub largely due to the presence of these institutions. The hypothesis is that, despite the prestigious image linked to the universities, there seems to be a distance between them and the city's population and that this phenomenon is strengthened by the rise of the extreme right-wing in Brazilian politics, guided by a conservatism and neoliberalism that drives public policies to dismantle education and privatize public sectors.
City versus university: a study about the dynamics between the citizens and the university lifestyle in São Carlos.
Keywords: Universidade; Conservadorismo; UFSCar; Nova direita; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS